Ghost boy [large type] : the miraculous escape of a misdiagnosed boy trapped inside his own body - Pistorius, Martin, 1975- (Center Point Large Print, 2015)
"With unflinching candor, Martin describes the chilling details of life as a secretly lucid vegetable--from the perversion of some who believed him to be brain dead, to the grace of those who sought recognition in his eyes"--